TosKer: A synergy between TOSCA and Docker for orchestrating multicomponent applications. (9th August 2018) - Brogi, Antonio; Rinaldi, Luca; Soldani, Jacopo
Summary: How to flexibly manage complex applications across heterogeneous cloud platforms is one of the main concerns in today's IT enterprise. The OASIS standard TOSCA (Topology and Orchestration Specification for Cloud Applications) and the Docker ecosystem are two emerging solutions trying to address this problem from different perspectives. In this paper, we propose a solution that tries to synergically combine the pros of both TOSCA and of Docker. More precisely, we propose a TOSCA‐based representation for specifying the software components and the Docker containers forming an application. We also present Tos Ker, an engine for orchestrating the management of multicomponent applications based on the proposed TOSCA representation and on Docker. Finally, we illustrate how Tos Ker was fruitfully exploited in a concrete case study based on a third‐party application.